2018
DOI: 10.1371/journal.pone.0206449
|View full text |Cite
|
Sign up to set email alerts
|

Improved islet recovery and efficacy through co-culture and co-transplantation of islets with human adipose-derived mesenchymal stem cells

Abstract: Islet transplantation is an established clinical procedure for select patients with type 1 diabetes and severe hypoglycemia to stabilize glycemic control. Post-transplant, substantial beta cell mass is lost, necessitating multiple donors to maintain euglycemia. A potential strategy to augment islet engraftment is the co-transplantation of islets with multipotent mesenchymal stem cells to capitalize upon their pro-angiogenic and anti-inflammatory properties. Herein, we examine the in vitro and in vivo effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 53 publications
2
39
0
Order By: Relevance
“…To determine islet yield, islets prior to and post 48-h culture were harvested and counted as previously described ( 36 ). Briefly, aliquots from both experimental and control groups were stained with dithizone (Sigma Aldrich, USA) and counted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine islet yield, islets prior to and post 48-h culture were harvested and counted as previously described ( 36 ). Briefly, aliquots from both experimental and control groups were stained with dithizone (Sigma Aldrich, USA) and counted.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis of the cultured islets was assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay (TUNEL)staining and flow cytometry as previously described (36)(37)(38). For TUNEL staining analysis, briefly, islets were collected and fixed in 4% paraformaldehyde, embedded in 3% agar (A8190, Solarbio) to create a solid cellularmatrix interaction, then processed and embedded in paraffin.…”
Section: Assessment Of Islet Apoptosismentioning
confidence: 99%
“…In both applications, large numbers of functional beta cells are required, but beta cells rapidly lose their functionality when expanded in vitro. The loss of beta cell functionality in vitro can be prevented by cocultivation with MSCs, which not only stimulate beta cell proliferation but also enhance their glucose-dependent secretion of insulin [97][98][99].…”
Section: Cocultivation Of Mscs With Other Cellsmentioning
confidence: 99%
“…Several studies have confirmed the positive effect of MSCs on islet viability and function through paracrine interactions and/or direct contact both in the culture period and after transplantation (Rackham et al, 2014[ 29 ]; Scuteri et al, 2014[ 35 ]; Yamada et al, 2014[ 42 ]). Some report that the protective effect of MSCs on cultured islets occurs via direct contact and the production of extracellular matrix molecules and annexin A1 (Arzouni et al, 2017[ 2 ]; Gamble et al, 2018[ 11 ]; Montanari et al, 2017[ 24 ]). This is while others suggest that indirect co-culture systems involving TranswellÂŽ inserts or conditioned media of MSCs (MSC-CM) could also inhibit apoptosis and promote islet viability and function through the secretion of trophic factors (de Souza et al, 2017[ 8 ]; Schive et al, 2017[ 34 ]; Yamada et al, 2014[ 42 ]).…”
Section: Introductionmentioning
confidence: 99%